ANALISIS YURIDIS PENERAPAN SANKSI BAGI PELAKU TINDAK PIDANA KORUPSI BERUPA PERAMPASAN ASET SEBAGAI UPAYA PENGEMBALIAN KERUGIAN NEGARA - Indra, Permana; Panjaitan , Hulman; Hutahaean, Armunanto (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The objectives of this research are 1) to contribute ideas and enrich the concepts and understanding of legal theories regarding Corruption Crimes committed by state officials, especially regarding law enforcement based on Law No. 20 of 2001 in conjunction with Law No. 31 of 1999 concerning Eradication of Corruption and the Criminal Code and the use of criminal law in corruption crimes related to the Application of Sanctions for Corruption Offenders in the Form of Asset Forfeiture as an Effort to Restore State Losses (Case Study of Decision Number: 2614 K/Pid. Sus/2021); and 2) to contribute thoughts in accordance with the bisertag in question which philosophically as a valuable learning process for scientific work and the application of legal discipline theory, as well as the results of writing library material as further Criminal law studies. The research method used is normative juridical research method, with the nature of descriptive research and also uses a statutory and case approach. The results of this research, there are differences of opinion between the Panel of Judges at the first and the appellate level in determining the actions and mistakes of the defendant who was convicted of violating Article 2 paragraph (1) of the Law in conjunction with Article 18 of Law Number 31 of 1999 as amended and corrected by Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 in conjunction with Article 64 paragraph (1) of the Criminal Code as described in the First Primary charge.